1997
DOI: 10.1074/jbc.272.13.8671
|View full text |Cite
|
Sign up to set email alerts
|

The Enhanced Immune Response to the HIV gp160/LAMP Chimeric Gene Product Targeted to the Lysosome Membrane Protein Trafficking Pathway

Abstract: The lysosome-associated membrane proteins (LAMP), found in the outer membrane of lysosomes and also in a multilaminar compartment that contains major histocompatibility complex class II (MHC II) proteins, are directed to their localization by a cytoplasmic carboxylterminal sequence. Our studies of the immune response to LAMP-targeted proteins has led to the application of a HIV-1 gp160/LAMP chimeric gene as a novel means to enhance the MHC II presentation of gp160. Immunofluorescence microscopy confirmed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
8

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 49 publications
1
38
1
8
Order By: Relevance
“…Processing of the proteins to yield the WT and ⌬V3 gp120 was first apparent at 60 min and more so at 120 min. The gp160 protein bands were present at each time point throughout the experiment, consistent with previous results that only a fraction of the gp160 protein is processed to the constituent gp120 and gp41 subunits (48). Beginning at 60 min, the intensity of the ⌬V3 mutant gp160 band was decreased by 71% relative to the value observed at 15 min, and at 240 min, the intensity decreased by over 90% as determined by densitometry.…”
Section: Resultssupporting
confidence: 74%
“…Processing of the proteins to yield the WT and ⌬V3 gp120 was first apparent at 60 min and more so at 120 min. The gp160 protein bands were present at each time point throughout the experiment, consistent with previous results that only a fraction of the gp160 protein is processed to the constituent gp120 and gp41 subunits (48). Beginning at 60 min, the intensity of the ⌬V3 mutant gp160 band was decreased by 71% relative to the value observed at 15 min, and at 240 min, the intensity decreased by over 90% as determined by densitometry.…”
Section: Resultssupporting
confidence: 74%
“…Therefore, we pursued alternative methods to establish a single rVV vector capable of infecting a single DC population capable of stimulating both CD4 ϩ and CD8 ϩ T cells. Using a molecular approach that directly targeted pp65 into the lysosomal compartment to facilitate presentation in the context of MHC class II (17)(18)(19)(20)(21)(22), we observed that the intracellular processing machinery for the class II pathway in DC remains intact for at least 16 h after the delivery of a maturation signal, and that such mature infected DC can effectively induce CD4 ϩ T cell responses. Moreover, the hybrid pp65 protein fused to both the LAMP1 transmembrane-cytoplasmic tail and an ER sorting signal did not interfere with concurrent processing of the protein via the class I pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wu and colleagues showed that linking the sorting signals of LAMP1 to the cytoplasmic/nuclear human papilloma virus E7 Ag routed this endogenously synthesized Ag into the MHC class II pathway, resulting in enhanced presentation to CD4 ϩ cells both in vitro and in vivo (17,19). The use of LAMP1-targeting sequences to improve MHC class II Ag presentation has also been shown with HIV gp160 (18,20,21), EBV, and influenza virus (22).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
See 1 more Smart Citation
“…With a variety of plasmids, antigens, and gene delivery systems, LAMP/antigen chimeras were targeted to the lysosomal membrane and found to elicit enhanced immune responses as compared with vaccines encoding unmodified, native antigens. Antigen/LAMP chimeras encoded in vaccinia virus vectors included HIV-1 gp160/LAMP (33,34), human papilloma virus E7/LAMP (35,36), and cytomegalovirus pp65/LAMP (37). Naked DNA plasmid antigen/LAMP chimera vaccines include human papilloma virus E7/LAMP (38) and dengue virus 2 premembrane/envelope/LAMP (39,40).…”
Section: Mhc 1 Ii-directed Antigen Activation Of Cd4 ϩ T-cells Is Vitmentioning
confidence: 99%